Aging : modern theories and therapies - Panno, Joseph (New York : Facts on File, 2011)
Examination of aging from natural process to technological developments that describes the most up-to-date research into extending the human life span
Includes bibliographical references (p. 223-235) and index
Keywords: Aging; Longevity